2014
DOI: 10.1589/jpts.26.111
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Improves Cardiac Autonomic Nervous System Activity in Type 1 Diabetic Children

Abstract: [Purpose] We investigated the effect exercise training has on cardiac autonomic nervous system (ANS) and cardiovascular risk profiles in children with type 1 diabetes mellitus (DM). [Subjects] Fifteen type 1 DM children (all boys; 13.0±1.0 years of age) were enrolled in the study. [Methods] The subjects received exercise training three times a week in a 12-week program. Each child was asked to walk on a treadmill to achieve an exercise intensity of VO2max 60%. ANS activity was measured by power spectral analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
(44 reference statements)
2
29
0
2
Order By: Relevance
“…Two of the four studies (Gusso et al., ; Nguyen et al., ) showed an overall significant reduction in VO 2 max, particularly in diabetics with poor glycemic control ( p < .05). In comparison, there was no statistical difference between diabetic and control adolescents after exercise compared with before exercise ( p > .05) (Adolfsson et al., ; Shin et al., ). It is notable that cardiorespiratory fitness can be maintained with light‐ to moderate‐intensity exercise and good glycemic control in children and adolescents with T1D.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Two of the four studies (Gusso et al., ; Nguyen et al., ) showed an overall significant reduction in VO 2 max, particularly in diabetics with poor glycemic control ( p < .05). In comparison, there was no statistical difference between diabetic and control adolescents after exercise compared with before exercise ( p > .05) (Adolfsson et al., ; Shin et al., ). It is notable that cardiorespiratory fitness can be maintained with light‐ to moderate‐intensity exercise and good glycemic control in children and adolescents with T1D.…”
Section: Resultsmentioning
confidence: 97%
“…The five remaining studies yielded relatively consistent results about glycemic control and PA. Regardless of type, duration, and frequency of the exercise, four studies (Gusso et al., ; Nguyen et al., ; Shin et al., ; Tomar et al., ) showed no significant associations between PA and HbA1c. In the fifth study by Carabott Pawley et al.…”
Section: Resultsmentioning
confidence: 99%
“…Green et al (2008) demonstrated that adaptation to exercise induced a decrease in resting blood pressure, which is similar to antihypertensive drug therapy. These changes in blood pressure may be associated with changes in its autonomic regulative function as both blood pressure and cardiovascular autonomic function can be improved with exercise training (Pagani et al 1988;Loimaala et al 2003;Timmers et al 2004;Shin et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Interventions to increase physical activity in paediatric T1DM have commonly focussed upon structured aerobic or resistance exercise training [11, 20]. These interventions work well for young people who are already active but for those children who are less active, promoting lifestyle physical activity (such as walking, active play, etc.)…”
Section: Introductionmentioning
confidence: 99%